Effect of Mindfulness-Based Cognitive Therapy on Symptoms of Depression: A Systematic Review - Fiddaroini, Fakhrun Nisa'; Yusuf, Ah.; Rachmawati, Praba Diyan (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Depression is a common mental health disorder. The main symptoms of depression are a lack of interest in the activities of daily life and suicidal thoughts. Mindfulness-based cognitive therapy (MBCT) is effective in preventing or reducing symptoms of depression. This study aimed to determine the effectiveness of mindfulness-based cognitive therapy in reducing symptoms of depression. This systematic review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Five databases included in this study This systematic review uses 10 articles that fit the inclusion criteria outcome. The result showed mindfulness-based cognitive therapy intervention from the research was reviewed significantly and has been shown to be an effective psychological intervention for reducing depressive symptoms in various populations. Mindfulness-based cognitive therapy has better results for reducing depressive symptoms and has a positive impact on reducing mental health problems and can be used by nurses and other mental health practitioners.